2013
DOI: 10.1080/08927014.2013.790014
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of interactions between the temperature field and biofouling in a synthetic treated sewage stream

Abstract: Biofouling causes significant losses in efficiency in heat exchangers recovering waste heat from treated sewage. The influence of the temperature field on biofouling was investigated using a flat plate heat exchanger which simulated the channels in a plate and frame unit. The test surface was a 316 stainless steel plate, and a solution of Bacillus sp. and Aeromonas sp. was used as a model process liquid. The test cell was operated under co-current, counter-current, and constant wall temperature configurations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Previous studies [11,41] have shown that the thermal resistance of the biofilms were linearly correlated with the biofilm thickness and the wet weight. In this study, the thermal resistance is of the main interest and the wet weight of the biofilms, instead of the cell count or the dry biomass, was measured.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies [11,41] have shown that the thermal resistance of the biofilms were linearly correlated with the biofilm thickness and the wet weight. In this study, the thermal resistance is of the main interest and the wet weight of the biofilms, instead of the cell count or the dry biomass, was measured.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study [41] has shown that the dominant bacteria of the treated sewage in six Beijing sewage plants was Bacillus sp. (>62%).…”
Section: Organism and Inoculummentioning
confidence: 99%
See 1 more Smart Citation
“…(gram-positive) and Aeromonas sp. (gram-negative) accounted for more than 80% of the biomass in suspension and 95% of the organisms forming biofilms [23].…”
Section: Biofouling Testsmentioning
confidence: 99%
“…It considers the problem where three or more methods are avail-able, building on the characteristic behavior observed in many cases of biofouling illustrated in the fouling resistance-time (Rf-t) data [12] in Figure 1. The three phases of fouling growth reported by reference 1 are evident:…”
Section: Introductionmentioning
confidence: 99%